RITUAL KREMASI ETNIS TIONGHOA DI RUMAH DUKA RUMBAI PEKANBARU - Depi Madona; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Death is a thing that can not be rejected, but death is fear by everyone. Generally,theTionghoa belief is based on the belief that the world of people's life is a reflection of theuniverse. Any death that happens to a family member of the heir or any other family memberwill perform a death ritual as a form of last respects. The death ceremony in this Tionghoacommunity can be done by being buried or cremated.Cremation is the application of the release of the corpse by burning. This ceremony is doneat the heirs home or in the house of grief which held by a foundation. In addition, this funeralwith a cremation is not only done by ethnic Tionghoa who are Buddhists. Tionghoa Ethnicwho are Catholic, Christians also perform the funeral ceremony by means of cremation. Forthat researchers tried to address how the implementation procedure of the cremationceremony. The results showed that the implementation of cremation rituals through severalstages: (1) Family meetings attended by close family. This meeting was conducted to find amutual agreement on where the corpse was located, the length of the body was held and theelection of a good day for each ceremony process. (2) Preparation by the family in the formof cleaning the body, wearing clothes on the corpse and some offerings. (3) Preparation bythe funeral home in the form of room decoration, (4) Ceremony before entering the crate. (5)The end of the deceased. (6) Tutu ceremony crate. (7) Funeral / cremation ceremony. (8)Taking ashes made one day after the cremation ceremony. This cremation ceremony isperformed in order to fulfill the last request of the deceased or a hereditary tradition that isbelieved in the community group itself. In addition there are several factors behind thecremation ceremony conducted on the community itself, one of the main factors is theeconomic factor.Keywords: Ritual, Cremation, Tionghoa